TRANSFORMASI DIGITAL DALAM MANAJEMEN KEUANGAN SYARIAH: PELUANG DAN TANTANGAN - Sari, Winda Novita; Albahi, Muhammad; Andrini, Rozi (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2025)
This study aims to analyze the influence of digital transformation on Islamic financial management and to identify the opportunities and challenges arising from its implementation. The research method used is a qualitative literature review by analyzing secondary data from journals and official reports published between 2019 and 2024. The findings indicate that digital transformation plays a vital role in improving efficiency, transparency, and financial inclusion through technologies such as FinTech, Blockchain, Big Data, and Artificial Intelligence. Nevertheless, significant challenges such as low digital literacy, sharia compliance issues, and inadequate regulatory frameworks remain. This research contributes to strengthening the literature on integrating digital innovation and maqashid alshariah principles to support the sustainability of Islamic finance in the digital era.